Stroke metric changes pre- vs. postroutine anesthesiologist involvement for endovascular treatment of acute ischemic stroke - Rall, Natalie; Orr, Walter N.; Nazir, Niaman; Giron, Grace; Plaza, Erin (Frontiers in Anesthesiology, 2024)
Background: Timing of endovascular treatment (EVT) for acute ischemic stroke (AIS) is important for patient outcomes. Studies have evaluated how anesthesia type may affect patient outcomes and timing of EVT for AIS, but there is limited data regarding how the presence of an anesthesia team can affect these metrics. The study aimed to compare time metrics and patient outcomes pre-versus post-routine involvement of a dedicated anesthesia team with EVT cases.Methods: All patients at our institution between 18 and 100 years old that were evaluated for stroke and determined to be candidates for EVT between November 2018 and November 2020 were considered for this study. Time metrics associated with EVT, which are commonly tracked by stroke centers, were compared pre-versus post-routine involvement of a dedicated anesthesia team in EVT cases. Secondary outcomes included modified Rankin Score at time of discharge, NIH Stroke Scale score at time of presentation and discharge, and incidence of intraprocedural hypotension.Results: 255 patients were included. Comparing pre-(n=119) vs post-neuroanesthesia team involvement (n=136) in EVT for AIS, there was a statistically significant decrease in median time from puncture to TICI score >2b in the in-house group from 49.00 minutes pre-involvement to 23.00 minutes post-involvement (P = 0.02) and puncture to TICI > 2b (39.5 vs 34 minutes, P = 0.01) for all patient categories when controlling for anesthesia type. The incidence of intraprocedural hypotension (MAP < 65 mmHg) also decreased significantly from 79% to 44% (P = 0.04), though it was not significant when controlling for anesthesia type (P = 0.05).Conclusions: Routine involvement of a dedicated anesthesia team for EVT in AIS patients could potentially improve stroke metrics and patient outcomes, though more studies are necessary to validate this model of care.